Pudarìne and pudár songs in south Baranja - Predojević, Željko (Anafora, 2022)
The paper presents pudarine – the annual custom of guarding ripening grapes which is celebrated in South Baranja in the second half of the summer, during the grape ripening season. At the heart of the celebration is the guarding of the grapes. The aim of the paper is to describe the custom, as well as to reveal the true reasons behind the celebration. Guarding the grapes was just an excuse for accompanying circumstances that contribute to the true value of the custom, namely meeting new people and preparing young women for marriage.